ANALISIS WACANA LAGU “JAR OF THE HEARTS” OLEH CHRISTINA PERRI DAN “SKYSCRAPER” OLEH DEMI LOVATO. - Ch. Evy Tri Widyahening Ayu Istiana Sari (Exsplorasi, 2015)
Discourse Analysis is one of the subject matters in the seventh semester in English Department, Teacher Training and Education Faculty, Slamet Riyadi University. In this research, the researchers conducted Discourse Analysis for two English songs. This research is aimed to peel up the content of the songs, which are sung by Christina Perri and Demi Lovato, from the perspectives of meaning, purpose, and the vision of the writers. Contextual aspects and inferential meaning can be seen from those songs. Grammatical aspects and lexical meaning are used to see the cohesion and coherence of those songs.This research is library research. Then, it used Miles and Huberman‟s theory of qualitative data analysis. The location of the research was in libraries of Unisri, UNS, UGM, and Balai Bahasa Semarang. The expert of Discourse Analysis for this research is Prof. Dr. Sumarlam, M.S. from UNS Surakarta. The output of this research are: (1) to publish an article in scientific journal which has ISSN (after finishing the research in one semester).; (2) to report the research result that can be used as a reference for students who study Discourse Analysis in English Department, Teacher Training and Education Faculty, Unisri.The research result shows that there were contextual aspects and inferential meaning, grammatical aspects and lexical meaning in the songs of „Jar of The Heart‟ by Christina Perri and „Skyscraper‟ by Demi Lovato which are obtained by conducting Discourse Analysis.Key Words: Coherent, Cohesion, Context and Inferential, Discourse Analysis, Christina Perri, and Demi Lovato.